Multifocal Recurrent Microcystic Adnexal Carcinoma. Issue 7 (October 2020) - Teixeira, Jeffrey C.; Patel, Vishal; Goodman, Joseph
Abstract : Abstract: Microcystic adnexal carcinoma (MAC) is a rare and locally aggressive neoplasm with preponderance for local recurrence but rarely nodal or distant metastasis. A 38-year-old male was referred to our clinic for definitive treatment of known recurrent and concern for multifocal MAC from previous biopsy. The patient was treated with modified Mohs and reconstruction with an anterolateral thigh (ALT) free flap for tissue coverage. This case highlights the rare nature of multifocal MAC, treatment challenges of Mohs clearance versus wide local excision, and reconstructive challenge associated with large post treatment defects.